PRINCIPLES OF PROTECTION AND CONSERVATION OF WATER RESOLUTIONS IN UZBEKISTAN - Narmirzayeva N. B. (Western European Studies, 2024)
This article talks about the skills of conservation and protection of water, which is an invaluable gift of nature, its role and importance in human life, as well as the measures implemented by our government to protect water resources in our country
Keywords: Water resources; Legal basis; Use; distribution